The Economic Effects of Long-Term Climate Change: Evidence from the Little Ice Age - Waldinger, Maria (Journal of Political Economy, 2022)
Recent studies consistently find important economic effects of year-to-year weather fluctuations. I study the economic effects of long-term and gradual climate change over 250 years in the Little Ice Age (1600–1850), during which people and economies had time to adapt. Results show significant negative economic effects of long-term climate change. Temperature impacted the economy through its effect on agricultural productivity and mortality. To adapt to the Little Ice Age, economies increased trade and changed land use. I discuss the relevance of these results for understanding the impact of today’s climate change, especially in developing countries.